2017
DOI: 10.1101/108191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncharacterized bacterial structures revealed by electron cryotomography

Abstract: 23 24 Running title: ECT of novel bacterial structures 25 26 Keywords: bacteria, electron cryotomography, cryo-EM, bacterial ultrastructure, 27 uncharacterized structures 28 29 30 2 SUMMARY STATEMENT 31 Here we present a survey of previously uncharacterized structures we have observed in bacterial 32 cells by electron cryotomography, in the hopes of spurring their identification and study. 33 34 ABSTRACT 35 Electron cryotomography (ECT) can reveal the native structure and arrangement of 36 macromolecular compl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…Dehiscence within bacteria, including V. cholerae, has previously been described and it has been associated with the transition to viable but non-culturable states, in which cells have a very low metabolic activity (Brenzinger et al, 2019;Shi et al, 2021). As noted in previous research, V. cholerae also expresses unknown structures in response to stressful environments (Dobro et al, 2017). In this study, we also observed unknown structures including the previously described 'wavey filament' and several types of other filaments (Suppl.…”
Section: Discussionsupporting
confidence: 86%
“…Dehiscence within bacteria, including V. cholerae, has previously been described and it has been associated with the transition to viable but non-culturable states, in which cells have a very low metabolic activity (Brenzinger et al, 2019;Shi et al, 2021). As noted in previous research, V. cholerae also expresses unknown structures in response to stressful environments (Dobro et al, 2017). In this study, we also observed unknown structures including the previously described 'wavey filament' and several types of other filaments (Suppl.…”
Section: Discussionsupporting
confidence: 86%
“…However, the S. rosetta genome has undergone extensive horizontal gene transfer from bacteria and other organisms (Matriano et al, 2021), so it is possible that the barbs could have an ancient bacterial origin. Indeed, the barb structures most closely resemble the size, shape, and general distribution of an uncharacterized bacterial complex in Prosthecobacter debontii , though the bacterial structures exhibit a 5-fold rather than 4-fold symmetry (Dobro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such ribbons were absent in wild‐type or other mutant tomograms and may represent a terminal organelle substructure that has failed to fold or localize correctly in the absence of the paired rods of the core, which may serve to orient normal core assembly. Perhaps significantly, segmented filamentous structures, sometimes bundled, were also recently described in other bacteria (Dobro et al ., ).…”
Section: Resultsmentioning
confidence: 97%